KEPEMIMPINAN EFEKTIF BAGI GENERASI Z DALAM SISTEM PENDIDIKAN: TRANSFORMASIONAL, TRANSAKSIONAL, DAN INSTRUKSIONAL - Resyadilla Azkia; Nur Adzkia Kamilah; Marini; Aslamiah; Celia Cinantya (Komunitas Manajemen Kompetitif, 2025)
As a digital native generation, Generation Z needs flexible and relevant leadership. This study aims to provide a comprehensive overview of the concept of leadership that is relevant to Generation Z. The methodology used in this study is called literature review. Literature review is the process of finding and reading various books, journals, and publications related to the research topic to write about it. The results of the literature study indicate that Generation Z is most suited to the transformational leadership paradigm because it emphasizes inspiration, individual growth, and collaborative vision. They need the meaning, values, and engagement that Generation Z has. Effective Gen Z leaders are those who can successfully apply the three approaches mentioned above. They can then adjust their leadership style to suit the changing situation, individual needs, and organizational dynamics.